Does programmed cell death (apoptosis) play a role in the development of multiple organ dysfunction in critically ill patients? A review and a theoretical framework. - Papathanassoglou, Elizabeth; Moynihan, Jan; Ackerman, Michael John (My University, 2000)
Objectives: To critically review the current understanding of the pathophysiologic events leading to the development of secondary multiple organ dysfunction (MODS) in critical illness and to examine the role of apoptosis (programmed cell death) as a mechanism involved in the progression of MODS. Data Sources: Research and review articles published since 1982 on the pathophysiology of MODS, particularly the role of cytokines, reactive oxygen species, heat shock proteins, and apoptosis. Research and review articles on the physiology of apoptosis. Articles include human/animal and in vitro/in vivo studies. Data Extraction: The most prevalent mediating factors of MODS were examined for their potential to induce apoptosis, as reported in the literature. The combination of several of the above factors was also examined in terms of apoptosis-triggering potential. Data Synthesis: Specific pathophysiologic conditions related to the onset of MODS have been shown to affect apoptotic rates in organ tissue cells and their respective endothelial cells in animal and in vitro models. These conditions include the following: a) increased release of inflammation-related cytokines; b) increased production of oxygen free radicals associated with ischemia/reperfusion injury and states of low tissue perfusion; c) expression and release of heat shock proteins from tissue cells and the liver; d) elevated glucocorticoid concentrations after adrenal cortex activation; and e) release of bacterial products into the systemic circulation. Conclusion: The most important MODS-related pathophysiologic conditions known to date have been shown to affect programmed cell death rates in almost all cell types. Organ-specific cell death involving both parenchymal and microvasculature endothelial cells is conceivably underlying organ dysfunction. The hypothesis that increased apoptotic rates are involved in organ dysfunction may provide a unifying theory for the pathophysiology of MODS.
Keywords: Systemic inflammatory response syndrome; Multiple organ dysfunction syndrome; Apoptosis; Programmed cell death; Cytokines; Oxygen free radicals; Heat shock proteins; Glucocorticoids; Tumor necrosis factor; Interleukin-6; Interleukin-1; Interleukin-10; Nitric oxide; Prostaglandins